Comparative Study of Spiritual Emotional Freedom Technique (SEFT) Therapy and Murottal Therapy on Reducing Pain in Elderly with Hypertension - Febriana, Annisa; Lestari, Devi Hairina; Pefbrianti, Diana; Ifansyah, M.Noor (GLOBAL HEALTH SCIENCE GROUP, 2024)
Hypertension is still one of the diseases suffered by many elderly. Complementary therapy is a form of non-pharmacological therapy that is applied to help relieve symptoms due to hypertension. Therapy that can be given is Spiritual Emotional Freedom Technique (SEFT) and Relaxation Therapy listening to Murottal Al-Quran. This study aims to compare SEFT therapy and Murottal therapy to reduce pain in elderly with hypertension. This study used Quasy experimental design with pre test and post test. The samples in this study were 15 people in the SEFT group and 15 people in the Murrotal group in PPRSLU Budi Sejahtera. This study used non-probability sampling technique, consecutive sampling type. Data was measured with a visual analog scale (VAS) to measure pain felt by the elderly. Data were analyzed using the Mann Whitney statistical test. results showed that there was no difference between SEFT therapy and Murrotal therapy in reducing pain in hypertensive elderly (p Value 0.473). There is no difference between SEFT therapy and Murottal therapy in reducing pain in hypertensive elderly. Trials of effectiveness in both therapies showed Murottal therapy was more effective than SEFT therapy in reducing pain levels in elderly people with hypertension.